Objektifikasi Seksual terhadap Perempuan: Studi Kasus Ito Shiori, Haachu, dan Korban Pelecehan Lainnya di Jepang - Pravangesta, Rifqaiza; Iskandar, Kurniawaty (KIRYOKU, 2024)
This research is written to analyse one type of sexual harassment that occurs in society, which is sexual objectification, using interviews and personal information from Ito Shiori, the author of Black Box and several women who have voiced out in public or anonymously. The purpose of this research is to determine the types of sexual objectification which occur in daily life and to issue awareness to the readers on sexual objectification. This research uses the objectification theory which is rooted in radical-cultural feminism and is written using the descriptive-analysis method and literature studies, using data from books, journals and the internet. The result of this research is that the reader is able to find out sexual objectifications that occur in daily life based on existent cases and to open opportunities to protect victims of sexual harassment from similar behaviour while also preventing them from becoming perpetrators of sexual harassment